2018
DOI: 10.1016/j.marpolbul.2018.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in marine sediments near Rothera Research Station, Antarctica

Abstract: Antarctica and surrounding waters are often considered pristine, but may be subject to local pollution from tourism, fishing and governmental research programme activities. In particular, the quantification of microplastic pollution within the Antarctic Treaty area (south of latitude 60°S) has received little attention. We examined microplastic particle concentrations in sediment samples from 20 locations up to 7 km from Rothera Research Station. The highest concentrations of microplastic (<5 particles 10 ml) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(79 citation statements)
references
References 20 publications
4
70
0
5
Order By: Relevance
“…Although the MPs concentrations measured in this study were much lower than those reported by studies using similar collection methods in other oceans, the concentration of microplastics along the coastline and closer to the MZS was higher than at other sampling sites. Moreover, in samples collected close to the effluent of MZS sewage treatment plant, the majority of microplastics were fibers, suggesting domestic washing on the base as one of the most likely sources, similar findings to those reported by Reed et al (2018) and Munari et al (2017) who found higher concentrations of benthic microplastics from sampling locations near the scientific research stations. While Isobe et al (2017) concluded that the microplastic found at the stations closer to the Antarctic continent were probably arriving from northernmost areas, Cincinelli et al (2017) and Munari et al (2017) raised the important issue of the role of human presence in Antarctica as a source of plastic pollution.…”
Section: Microplastics In Antarctica: Presence Distribution and Posssupporting
confidence: 88%
See 1 more Smart Citation
“…Although the MPs concentrations measured in this study were much lower than those reported by studies using similar collection methods in other oceans, the concentration of microplastics along the coastline and closer to the MZS was higher than at other sampling sites. Moreover, in samples collected close to the effluent of MZS sewage treatment plant, the majority of microplastics were fibers, suggesting domestic washing on the base as one of the most likely sources, similar findings to those reported by Reed et al (2018) and Munari et al (2017) who found higher concentrations of benthic microplastics from sampling locations near the scientific research stations. While Isobe et al (2017) concluded that the microplastic found at the stations closer to the Antarctic continent were probably arriving from northernmost areas, Cincinelli et al (2017) and Munari et al (2017) raised the important issue of the role of human presence in Antarctica as a source of plastic pollution.…”
Section: Microplastics In Antarctica: Presence Distribution and Posssupporting
confidence: 88%
“…Interestingly, the authors observed a decreasing concentration of plastic debris at increasing distances from the Italian research station, suggesting local activities as the main source of these particles. Lastly, Reed et al (2018), examined microplastic concentrations in 60 sediment samples from 20 locations collected in 2016 by diving or box coring up to 7 km from Rothera Research Station (UK) in the Antarctic peninsula (Fig. 2).…”
Section: Microplastics In Antarctic Sediments and Beachesmentioning
confidence: 99%
“…The sampling technique may also have influenced the microplastics sampled, as previous studies in the open ocean found an effect of the SML sampling technique used on the abundance of various shapes of microplastic in the SML 29 . Numerous studies, however, have found a dominance of fibres in recovered plastics < 5 mm [35][36][37][38][39] .…”
Section: Discussionmentioning
confidence: 96%
“…A further pollution threat concerns the potential for loss, through burial, of fuel drums stored in remote locations to support deep-field activities, some of which need to be raised every 1-2 years (depending upon the snow accumulation rate). Lower research station occupancy will also result in lower volumes of sewage release to the environment, thereby temporarily reducing the release of pollutants, such as trace metals and microplastics, and non-indigenous microorganisms (Connor 2008, Power et al 2016, Reed et al 2018, Stark et al 2019, Webb et al 2020. Lower levels of visitation will reduce disturbance of wildlife, which may be particularly relevant in locations where wildlife population declines have been linked to tourism and national operator activity (Pfeiffer 2005, Coetzee & Chown 2016, Dunn et al 2019, https://www.umweltbundesamt.de/sites/ default/files/medien/461/publikationen/4424.pdf).…”
Section: Environmental Impactmentioning
confidence: 99%